Ductile failure Modeling : stress dependance, non-locality and damage to fracture transition - J. M. A. César de Sá (2015)
In this chapter, some recent developments and proposals for improvement of material models at the constitutive level to deal with ductile damage at large plastic strains are addressed. Numerical tests are carried out to test their performance on shear-dominated stress states where their main differences lie. Subsequently, aspects of the use of nonlocal models for the regularization of the numerical values associated with damage models, namely, discretization dependency, are reviewed. Different approaches on the choice of the regulation variable or variables are tested at different stress states characterized by different values of triaxiality and third invariant of the deviatoric stress tensor. Finally, a simple strategy on how to handle the transition from damage to fracture by means of the extended finite element method is described.